ANALISIS KINERJA DAN STRATEGI PENGEMBANGAN USAHA PADA ROSE FLORIST DI BANDAR LAMPUNG - Wenni Mey Kardepa Sembiring; Wuryaningsih Dwi Sayekti; Dame Trully Gultom (Lampung University, 2021)
This study aims to analyze the existing performance of the Rose Florist agro-industry and formulate the business development strategy. This research uses a case study method with three respondents consisting of business owner, an employee of the business, and an UMKM officer. Data collection was carried out in April-May 2020. Data analysis uses cash flow and SWOT. The results showed that the Rose Florist Agroindustry has a good financial performance. There was an increase in cash of 9,538,729.17 from the cash flow statement, from the first period of IDR 153,249,128.57 to the second period of IDR 162,787,857.74. The development strategies that can be used in the development of the Rose Florist Agroindustry are to make quality flower arrangements, to add business signposts in business locations, and to train the workers on good management and better skills. Keywords: agro-industry, performance, Rose Florist, strategy